Assessment of physico-chemical parameters of Tiru reservoir, Udgir in district Latur, Maharashtra - MARKAD, ADINATH T.; LANDG, ASHA T.; GORE, SANDEEP B.; SUTAR, VIJAY B.; KHARATMOL, BALAJI R. (Journal of Soil and Water Conservation, 2024)
Increasing demand and irresponsible use of water has put tremendous pressure on water resources. In the present study, twenty water quality parameters of Tiru Reservoir, Udgir in district Latur of Maharashtra state, India were analysed to determine the trophic status. The Sampling was conducted from August 2017 to January 2019 from five stations. The range of the selected water quality parameters showed significant differences for temperature (22-31ºC), alkalinity (79-149 mg/l), hardness (68.7-161.1 mg/l), dissolved oxygen (5.6-8.3 mg/l), carbon dioxide (0-8.93 mg/l), total phosphorus (8.6-44.05 μg/l) and chlorophyll-a (1.3-8.8 μg/l) during the study period. Summer season (36.55 μg/l) showed record values of total phosphorus as compared with winter readings (17.40 μg/l - 2017 and 15.41 μg/l - 2018) and monsoon (18.22 μg/l - 2017 and 24.78 μg/l - 2018). Seasonal variation in Chl-a was observed with peak values in the summer season (7.14 μg/l), moderate during monsoon 2018 (3.54 μg/l), and least values in winter (2.78 μg/l in 2017 and 2.49 μg/l in 2018). Elevated nutrient levels like phosphorus during the summer season boosted the plankton growth and raised the concentration of chlorophyll-a in the reservoir. Overall observations showed that Tiru reservoir is in eutrophic to a hyper-eutrophic condition almost throughout the study period. Human activities, such as the discharge of waste disposal and the overuse of agricultural fertilisers, contributed to the rise in pollution levels.